The Performance Of Cattle Dairy Business (Case Study In Senduro District, Lumajang Regency) - Vivin; Inggit Kentjonowaty; Dewi Masyithoh (UNIVERSITAS ISLAM LAMONGAN, 2025)
This study aims to analyze the performance of dairy cattle farming businesses in Senduro District, Lumajang Regency, by identifying factors that influence the production and income of farmers. The variables analyzed include the number of lactating dairy cattle, the amount of green fodder per day, the amount of additional feed per day, the age of farmers, education level, livestock farming experience, the number of household members, the number of workers, training that has been attended and extension in livestock farming. The approach used is quantitative descriptive with multiple linear regression analysis methods. The results of the study showed that simultaneously all independent variables had a significant effect (P <0.05) on the performance of livestock farming businesses. Partially, the variables of the number of lactating cows, the amount of concentrate feed, and the number of family members showed a significant effect (P <0.05) on the performance of dairy farming businesses in Senduro District. The conclusion of this study is that the success of dairy farming businesses is greatly influenced by the management of production inputs, especially in terms of the number of productive cows and the efficiency of feeding. This study is expected to be a reference in the development of dairy farming businesses and improving the welfare of farmers in highland areas.